Effect of TiO2 Rutile Additive on Electrical Properties of PPy/TiO2 Nanocomposite. (16th March 2016) - Nguyen, Trong Tung; Duong, Ngoc Huyen
Abstract : Polypyrrole/titanium dioxide nanocomposite (PPy/TiO2 ) was synthesized by in situ chemical polymerization of pyrrole (Py) monomer in colloidal suspension of TiO2 rutile. TEM and SEM images show that the TiO2 is covered by PPy forming a core-shell structure. The PPy/TiO2 core-shell will createn - p junction and bring in an inversion layer on the PPy-shell surface. The feature is accounted for the modification in electrical properties of the PPy/TiO2 nanocomposite. On the exposure to oxygen the conductivity of the nanocomposite exhibits an increase in 16–18-folds that are accounted for the interaction between oxygen (an electron acceptor) and the inversion layer. The cyclic voltammetry diagrams have shown that at around 15% TiO2 and scan rate 100 mV/s the nanocomposites can reach a specific capacitance about 176 F/g.